Spatial image compounding applied to a phase coherence corrected UT-PA technique for inspecting nuclear components of coarse-grained structure - Brizuela, Jose David (2016)
The aim of this work is to obtain a C-Scan view of an austenitic stainless steel weld from a nuclear use pipe. In order to obtain this result Sectorial Scans (S-Scan) from both sides of the weld are obtained by Ultrasonic Phase Array (UT-PA). Then, spatial image compounding is performed to generate a single image from the S-Scans acquired at the same circumferential position of the transducer. These joints have a coarse grain structure which significantly reduce the transmission of the ultrasonic wave due to attenuation characteristics and backscattered noise from microstructures inside the material. For this reason, phase coherence imaging technique has been also applied to reduce the structural noise and improve the image quality. To verify detected defects, and given the impossibility of cutting the component, gammagraphy were performed with Co60.